2007
DOI: 10.1088/1752-7155/1/1/011001
|View full text |Cite
|
Sign up to set email alerts
|

Acetone, ammonia and hydrogen cyanide in exhaled breath of several volunteers aged 4–83 years

Abstract: Original on-line measurements of acetone, ammonia and hydrogen cyanide in the exhaled breath of several volunteers within the age ranges 4-6 years and 60-83 years are reported and compared with previous data on volunteer cohorts covering ages 17-18 years and 20-60 years. The compiled data show that a significant statistical increase in breath ammonia occurs with increasing age, but that acetone and hydrogen cyanide do not vary greatly with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 10 publications
3
87
3
Order By: Relevance
“…Hydrogen cyanide has recently been the subject of several studies conducted with SIFT-MS. Medians of around 10 ppbv were found in the breath of children and senior adults byŠpaněl et al [8], who also reported a median of 8 ppbv in the breath of 26 young adults [4]. In contrast to these results, the majority of 200 healthy school children had breath HCN levels below 2 ppbv in a study conducted by Enderby et al [11].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hydrogen cyanide has recently been the subject of several studies conducted with SIFT-MS. Medians of around 10 ppbv were found in the breath of children and senior adults byŠpaněl et al [8], who also reported a median of 8 ppbv in the breath of 26 young adults [4]. In contrast to these results, the majority of 200 healthy school children had breath HCN levels below 2 ppbv in a study conducted by Enderby et al [11].…”
Section: Discussionmentioning
confidence: 92%
“…The concentration of hydrogen cyanide in human breath typically ranges from several parts per billion by volume (ppbv) to tens of ppbv [4,[7][8][9][10][11][12][13][14]. Systemic breath HCN may originate from metabolism, microorganisms, neutrophil-mediated cyanide generation [15] and enzymatic activity [7], or from exogenous sources such as food containing cyanogenic glycosides [16] and exposure to tobacco smoke or combustion gases.…”
Section: Introductionmentioning
confidence: 99%
“…However, one issue in breath acetone measurements, which is often neglected, is that many intra-individual biological parameters (age, gender, body mass index (BMI), etc.) influence the BA concentration [6][7][8][9]. Therefore, it would be insightful to study longitudinal variations of BA in given individuals that have no baseline effect resulting from individual physiological heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…The natural intra-individual biological and diurnal variability can easily cause wide variations in breath acetone concentration [7][8][9][10]. One of the ideal approaches to this end is the implementation of a rat model.…”
Section: Introductionmentioning
confidence: 99%